1999
DOI: 10.1074/jbc.274.48.34294
|View full text |Cite
|
Sign up to set email alerts
|

Direct Involvement of Phosphatidylinositol 4-Phosphate in Secretion in the Yeast Saccharomyces cerevisiae

Abstract: The SEC14 gene encodes an essential phosphatidylinositol (PtdIns) transfer protein required for formation of Golgi-derived secretory vesicles in yeast. Suppressor mutations that rescue temperature-sensitive sec14 mutants provide an approach for determining the role of Sec14p in secretion. One suppressor, sac1-22, causes accumulation of PtdIns(4)P. SAC1 encodes a phosphatase that can hydrolyze PtdIns(4)P and certain other phosphoinositides. These findings suggest that PtdIns(4)P is limiting in sec14 cells and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
273
1
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 266 publications
(288 citation statements)
references
References 64 publications
11
273
1
3
Order By: Relevance
“…In vegetative sec14(K66A K239A) cells, the synthesis of PtdIns(4)P is reduced (Phillips et al, 1999), and overexpression of the PtdIns 4-kinase Pik1p suppresses the growth defect of sec14-1 cells at semirestrictive temperature (Hama et al, 1999). Similarly, we found that overexpression of PIK1 could restore the sporulation of sec14-1 diploids to near wild-type frequency, and suppression of the meiotic defect was dependent on Spo14p (Table 2, lines 19 -20).…”
Section: Suppression Of Sec14 Sporulation Defect By Overexpression Ofmentioning
confidence: 54%
See 3 more Smart Citations
“…In vegetative sec14(K66A K239A) cells, the synthesis of PtdIns(4)P is reduced (Phillips et al, 1999), and overexpression of the PtdIns 4-kinase Pik1p suppresses the growth defect of sec14-1 cells at semirestrictive temperature (Hama et al, 1999). Similarly, we found that overexpression of PIK1 could restore the sporulation of sec14-1 diploids to near wild-type frequency, and suppression of the meiotic defect was dependent on Spo14p (Table 2, lines 19 -20).…”
Section: Suppression Of Sec14 Sporulation Defect By Overexpression Ofmentioning
confidence: 54%
“…Substantial evidence demonstrates that both sec14 and pik1 (Hama et al, 1999;Walch-Solimena and Novick, 1999) mutations block vesicle-mediated transport from the Golgi. That both sec14-1 and pik1-ts diploids are unable to carry out meiosis suggests that trafficking through the secretory pathway is required for meiotic progression.…”
Section: Phosphoinositide Function During Meiosismentioning
confidence: 99%
See 2 more Smart Citations
“…mSac1-GFP showed a higher degree of colocalization with the cis-Golgi marker GM130 than with the TGN marker TGN46 ( Figure 3A). The presence of mSac1 in Golgi cisternae (particularly TGN) is paradoxical given PtdIns-4-P is important for anterograde trafficking from the TGN (Hama et al, 1999;Walch-Solimena and Novick, 1999;Godi et al, 2004). One possibility is mSac1 is disqualified from efficient entry into Golgi subregions from which anterograde vesicles bud.…”
Section: Sac1 and Cargomentioning
confidence: 96%